Cross-sectional examination of extrapyramidal side effects in a specialist palliative care inpatient unit. Issue 3 (9th October 2018) - O'Brien, Hannah; Kiely, Fiona; Barry, Aileen; Meaney, Sarah
Abstract : Objectives: Extrapyramidal side effects (EPSEs) are serious potentially reversible side effects of antipsychotic and other medications that can cause distress for patients. A core principle of palliative care involves optimising quality of life. If side effects of medications are burdensome, it is imperative that we address this issue. The aim of the study was to determine and describe the burden of EPSEs in a specialist inpatient unit. Methods: Consenting patients who met inclusion criteria were assessed for EPSE with two validated screening tests, the Modified Simpson-Angus Scale (MSAS) and Barnes Akathisia Rating Scale (BARS). Additional demographic data were collected including medications associated with EPSE, previous history of EPSE and known risk factors that may predispose a patient to EPSE. Results: 43% inpatients met inclusion criteria. At least 66% of patients were taking regular medications associated with EPSE. Of those, 25% were taking ≥2 medications associated with EPSE. The MSAS revealed 50% scored <3, 44% scored 3–5% and 6% scored 6–11. Seven patients had at least one 'not rateable score'. In the BARS (sitting±standing), 94% scored 0/5 and 6% scored 1/5. 12.5% of participants were able to stand for 2 min to complete the BARS. Conclusions: 50% screened positive for EPSE. The complete BARS was unsuitable for most participants. The MSAS, while allowing a not rateable score, may underestimate EPSE. The frailty of an inpatient unit population impacts on applicability of screening tools and may therefore underestimate the burden of the problem in this population. Development of a population-specific screening tool warrants further investigation.